2015
DOI: 10.5194/bgd-12-12395-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of sedimentary alkalinity release on the water column CO<sub>2</sub> system in the North Sea

Abstract: Abstract. Recently, it has been proposed that alkalinity release from sediments can play an important role in the carbonate dynamics on continental shelves, lowering the pCO2 of seawater and hence increasing the CO2 uptake from the atmosphere. To test this hypothesis, sedimentary alkalinity generation was quantified within permeable and muddy sediments across the North Sea during two cruises in September 2011 (basin-wide) and June 2012 (Dutch coastal zone). Benthic fluxes of alkalinity (AT) and dissolved inorg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 102 publications
(31 reference statements)
1
7
0
Order By: Relevance
“…On annual basis, the A T residual in Ringkøbing Fjord before the regime shift was approximately 0.3–0.4 mmol kg −1 yr −1 (Figure b) corresponding to an average net areal flux of 1.6–2.1 mmol m −2 d −1 , similar to the estimate by Brenner et al () for the Southern North Sea. The conspicuous seasonal A T development in Ringkøbing Fjord thus appears to support substantial internal A T fluxes mediated by biogeochemical processes.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…On annual basis, the A T residual in Ringkøbing Fjord before the regime shift was approximately 0.3–0.4 mmol kg −1 yr −1 (Figure b) corresponding to an average net areal flux of 1.6–2.1 mmol m −2 d −1 , similar to the estimate by Brenner et al () for the Southern North Sea. The conspicuous seasonal A T development in Ringkøbing Fjord thus appears to support substantial internal A T fluxes mediated by biogeochemical processes.…”
Section: Discussionsupporting
confidence: 83%
“…Using the basin characteristics (Table ), the A T increase in Ringkøbing Fjord from April to September corresponds to an average areal flux of approximately 7.5 mmol m −2 d −1 . In fact, measurements by Brenner et al () at numerous sites in the Southern North Sea revealed sediment to water A T fluxes in a range 0–21.4 mmol m −2 d −1 (mean: 6.6 mmol m −2 d −1 ). In a numerical experiment, including A T sources and sinks in both sediments and water column, Brenner et al () calculated a net A T generation in the water column of 2.4 mmol m −2 d −1 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent studies have pointed out that the alkalinity generation in coastal sediments may increase the capacity of the coastal ocean to act as a potential sink for atmospheric CO 2 (Thomas et al 2009;Faber et al 2012;Brenner et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sedimentary alkalinity production can offset the effect of dissolved inorganic carbon production by respiration on the acidification of coastal waters, thus enhancing the uptake of atmospheric CO 2 (Hu and Cai 2011;Brenner et al 2016). For example, in M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%